Metode Pelaksanaan Basement Retaining Wall pada Proyek Pembangunan Rumah Sakit - Gultom, Sharon Simon; Fansuri, Muhammad Hamzah; Khalifah, Via Azizul Saputri; Heriyani, Hesti Putri (Journal of Research and Inovation in Civil Engineering as Applied Science (RIGID), 2025)
The construction of hospital infrastructure requires precise construction techniques, especially in areas with complex soil conditions. This study aims to analyze the implementation method of retaining walls in the basement of the RSPON project in Cawang, Jakarta. The study was conducted using a descriptive-analytical approach through field observations, documentation, and literature review. The main focus of the research is to identify the construction stages, types of materials, and techniques used in the construction of retaining walls. The results show that the selection of construction methods is adjusted to local geological characteristics, structural loads, and land stability requirements. The applied method provides an effective solution in overcoming technical challenges at the project site, considering safety, efficiency, and construction quality aspects. This research is expected to contribute to the development of retaining wall construction techniques for similar infrastructure projects, especially in areas with complex soil conditions.